(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
In the article the author has traced the formulation process of the concept «state of mind» in the psychological and literary dictionaries and identified notable contradictions in the statements. The author has formulated the chief problem in study of mentality and spirituality in the literary works.